2011
DOI: 10.4049/jimmunol.1002244
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Nerve–Mast Cell Interaction by a Neuronal Short Isoform of Cell Adhesion Molecule-1

Abstract: Close apposition of nerve and mast cells is viewed as a functional unit of neuro-immune mechanisms, and it is sustained by trans-homophilic binding of cell adhesion molecule-1 (CADM1), an Ig superfamily member. Cerebral nerve–mast cell interaction might be developmentally modulated, because the alternative splicing pattern of four (a–d) types of CADM1 transcripts drastically changed during development of the mouse cerebrum: developing cerebrums expressed CADM1b and CADM1c exclusively, while mature cerebrums ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 56 publications
3
51
1
Order By: Relevance
“…Hagiyama et al reported that the frequency of signal-transduction detection was~40% in their study (36). This percentage was similar to that of the cells indicating the higher breaking force (0.8 Â 10 À12 Ns), which is estimated to be 30-40% (Fig.…”
Section: Maturation Process Between the Neurites And Mast Cellssupporting
confidence: 67%
See 1 more Smart Citation
“…Hagiyama et al reported that the frequency of signal-transduction detection was~40% in their study (36). This percentage was similar to that of the cells indicating the higher breaking force (0.8 Â 10 À12 Ns), which is estimated to be 30-40% (Fig.…”
Section: Maturation Process Between the Neurites And Mast Cellssupporting
confidence: 67%
“…In a previous study, our group evaluated the adhesion behavior between neuroblastoma cells (neuro2a) and mast cells, in which several isoforms of CADM1 were expressed exogenously (36). The results indicated that the spatial distribution of CADM1s on the neurite differed among the isoforms, resulting in different adhesion strengths.…”
Section: Introductionmentioning
confidence: 99%
“…However, based on RT-PCR and sequencing of the obtained products, we demonstrated the occurrence of three exon 8c-containing transcript variants (i.e. 8abc, 8bc, and 8c), which were not identified in similar approaches performed previously to study developmental changes in the Syn-CAM 1 transcript pattern in the mouse brain (10,11).…”
Section: Discussionmentioning
confidence: 58%
“…IP, immunoprecipitation; WB, Western blot analysis. Notably, transcript variant 8abc showed a constantly low expression level throughout postnatal brain development, which might have hampered the identification of this variant in previous studies (10,11). Transcript variant 8c was hardly detectable before P7/P9 but was constantly expressed thereafter.…”
Section: Syncam 1 Transcript Variants Expressed During Postnatal Mousementioning
confidence: 95%
See 1 more Smart Citation